Criminal Liability of Defendants with Bipolar Disorder from the Perspective of Justice in Supreme Court Decision No. 1209 K/Pid.Sus/2023 - Virriantaka; Adhari, Ade (Jurnal Ilmu Hukum Kyadiren, 2026)
In Indonesia, criminal law stipulates that a person can only be held accountable for their actions if there is an element of fault, in addition to meeting the principle of legality. Criminal liability aims to determine whether the perpetrator should indeed bear the consequences of their actions. On the other hand, Bipolar Disorder is a serious mental condition that causes drastic mood changes, which can affect a person’s ability to control their behavior and actions. This study aims to examine the extent to which the principle of justice is applied in determining criminal liability for defendants suffering from Bipolar Disorder, as illustrated in Supreme Court Decision Number 1209K/Pid.sus/2023. The methods used include the Statute Approach and the Case Approach. The findings show that the provisions regarding criminal liability are contained in Article 44 of the former Criminal Code (KUHP) as well as Articles 38 and 39 of the new Criminal Code (Law Number 1 of 2023). However, in practice, the judges’ decision has not been entirely fair, as the defendant’s Bipolar Disorder was not taken into consideration. In fact, criminal law should not only focus on punishment but also take into account the condition of the perpetrator, including the defendant’s mental state. By doing so, the imposed sentence can be more humane and appropriately targeted.